Complete book of rules - Fein, Ellen ([S.l.] : Thorsons, 2000)
Everything you need to know to capture Prince Charming's heart. The very best advice from The Rules and The Rules 2 is brought together to provide the ultimate guide to successful dating. The notorious dating handbook which, comprises many tips such as 'Never call a man first' etc (designied to make Mr Right hungry for more) whcih although old-fashioned have been found effective by millions of women worldwide. Other essential advice offered: / Always end the first date -- it will leave him desperate for more / Don't call him -- it will make him desire you more / Never accept a Saturday night date after Wednesday -- it will encourage him to phone sooner / Always end the telephone conversation first -it will leave him wanting more / Don't rush into sex -- let his passion build / On the first date, don't stare romantically into his eyes -- he'll know you are planning the honeymoon.